1973
DOI: 10.1097/00132586-197302000-00054
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiorespiratory Effects of Thoracic Epidural Anaesthesia

Abstract: The cardio-respiratory effects of a thoracic epidural anaesthetic as is given for pain relief following upper abdominal surgery were examined in thirteen surgical patients studied in the immediate pre-operative period.following an overnight fast and without premedication.The focus of interest was on its effects on FRC and on gas exchange (measured as A-aD02 and OS/OT%), waich have not been previously reported. AlI subjects were given 10 ml/Kg glucose in saline I.V. during the pre-epidural periode Lidocaine 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

1983
1983
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
3
0
3
Order By: Relevance
“…The reason for this difference is not known. Studies of functional residual capacity during epidural block have not shown any significant changes from that of the control state (6,18). In our study, as in the study by McCarthy (6), no significant changes were seen in F R C or in closing capacity.…”
Section: Discijssionsupporting
confidence: 68%
“…The reason for this difference is not known. Studies of functional residual capacity during epidural block have not shown any significant changes from that of the control state (6,18). In our study, as in the study by McCarthy (6), no significant changes were seen in F R C or in closing capacity.…”
Section: Discijssionsupporting
confidence: 68%
“…20 In contrast with the latter results, and in line with our study, others have not found that EDA has any influence on spirometry or lung dynamics. [21][22][23][24] During forced expiration (e.g. spirometry), the principal expiratory muscles are those of the abdominal wall and, to a lesser extent, the internal intercostal muscles.…”
Section: Thoracic Epidural Analgesia and Respiratory Functionmentioning
confidence: 99%
“…This is the first study in children examining the impact of a neuroaxial blockade on FRC. Only studies performed in adults are available to compare our findings on the effect of epidural anaesthesia on FRC [17][18][19][20][21]. While some of the adult studies found no effect of lumbar or thoracic epidural anaesthesia [18][19][20], others showed a decrease [21] or an increase in FRC [17].…”
Section: Discussionmentioning
confidence: 88%